Polyploidy Breeding of African Nightshade ( Solanum section Solanum ) - Agong', Stephen G.; Ojiewo, Christopher O.; Murakami, Kenji; Masinde, Peter W. (Global Science Books, 2007)
The perception of African nightshades ( Solanum section Solanum ) as “healthy” foods, supported by documentation of their high nutri- tional and medicinal benefits, has led to a sudden and steady upsurge in their consumption, demand and monetary value in Africa and most parts of South-East Asia. However, due to very low leaf yields, production of these vegetables remains on small-scales, re sulting in acute shortages and escalating prices, especially in urban areas. Apart from local variants or landraces selected in some regio ns where these plants are utilized as food and/or me dicinal plants, there are no improved cultivars developed through conventional plant breeding techniques. Species belonging to this section, generally referred to as “ Solanum nigrum -complex” are predominantly autogamous, favour- ing production of many small fruits and seeds, which compete with leaves for photosynthates. S . nigrum -complex constitutes a polyploid series, with diploid (2 n =2 x =24), tetraploid (2 n =4 x =48), hexaploid (2 n =6 x =72) and rarely, octoploid (2 n =8 x =96) species, a trait that can be exploited for cultivar development. This review outlines the possi ble evolutionary mechanisms and modes of origin of the polypl oids, breeding strategies to produce heteroploids such as triploid (2 x =3 x =36), pentaploid (2 n =5 x =60) and heptaploid (2 n =7 x =84) from existing or induced polyploids and envisaged advantageous properties of the novel polyploids or heteroploids over their wild-type progen itors. With few exceptions, heteroploidy is known to cause sterility or highly reduced fertility of both pollen and ovules. The Africa n nightshade heteroploid series would putatively be male- and female-sterile, thus eliminating fruit- and seed-set and enhancing leaf produc tivity.
Keywords: breeding strategies; heteroploidy; leaf yield; Solanum nigrum- related species